Lesser Cornstalk Borer, Elasmopalpus lignosellus (Zeller) (Insecta: Lepidoptera: Pyralidae) - John L. Capinera (EDIS)
The lesser cornstalk borer, Elasmopalpus lignosellus (Zeller), was described by Zeller in 1848, but it was not considered of economic importance until 1881 (Riley 1882). It is a pest of several economically important crops. This document is EENY-155, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: September 2000.